Implementation of outcome-based education (OBE) in UPM : student learning outcomes (SLOs) in UPM - Mohayidin, Mohd Ghazali; Mustafa, Ghazali; Suandi, Turiman; Baki, Roselan; Kamaruddin, Norfaryanti; Man, Nor Azirawani; Adam, Azura; Abdullah, Siti Norziah (2007)
The move towards applying outcome-based education (OBE) in teaching and learning at tertiary education level has become one of the most important topics ;n recent years. Education authority is giving greater attention to evaluate outcomes of education projects. Apart from the three learning domains; namely, cognitive, psychomotor and affective, the Ministry of Higher Education (MoHE) has determined and listed eight learning outcomes for higher education institutions. These learning outcomes are important in providing wholesome quality education to students. The Centre for Academic Development at UPM has conducted a study starting from the second Semester of the 2005/2006 academic year to determine the extent to which these learning outcomes have been achieved. Results of the study will be used to develop effective intervention strategies that can be practiced to achieve the desired SLOs. This includes the development of: guidelines for identifying and defining SLOs, strategies for selecting suitable teaching approaches, guidelines for selecting appropriate assessment techniques and development of policies and guidelines to implement OBE. Questionnaires were distributed to UPM lecturers and the data were analysed using descriptive statistics. The result shows the overall achievement according to different domains were as follows: cognitive domain was at level 4, psychomotor domain at level 4 and affective domain at level 3. The Ministry's set of learning outcomes revealed the following result: The highest score went to the outcome of providing knowledge to students, While the least achievable learning outcome was managerial and entrepreneurial skills. The results infer low order thinking skills were highly observable and soft-skills among students were lacking and this problem needs to be addressed quickly and effectively.